Philosophy through computer science. - Lim, D.
In this paper I hope to show that the idea of teaching philosophy through teaching computer science is a project worth pursuing. In the first section I will sketch a variety of ways in which philosophy and computer science might interact. Then I will give a brief rationale for teaching philosophy through teaching computer science. Then I will introduce three philosophical issues (among others) that have pedagogically useful analogues in computer science: (i) external world skepticism, (ii) numerical vs. qualitative identity, and (iii) the existence of God.
Keywords: Philosophy -- Periodicals; Teaching -- Periodicals